The Canaanite women in Korean context: A postcolonial feminist reading of Matthew 15:21–28 - Chung, Yonghan (HTS teologiese studies, 2025)
This study explores Matthew 15:21–28 through a postcolonial feminist criticism, comparing the Canaanite woman in the Roman Empire with the North Korean women in South Korea to expose the dynamics of imperialism, androcentrism and patriarchal power. By challenging androcentric and Christ-centric interpretations that often overshadow the woman’s agency and voice, the analysis highlights the woman’s act of crossing boundaries, building a new identity and claiming participation in the table as acts of resistance. Parallels are drawn between the Canaanite woman and North Korean women, who similarly navigate boundaries and confront marginalisation within androcentric and imperial frameworks. North Korean women’s crossings highlight their struggle for survival amid poverty and human rights violations, as well as their efforts to construct a new identity within South Korea’s discriminatory context and to claim participation in the table amid neo-imperial context of two Koreas. The study advocates for a redefinition of communal inclusion, challenging dominant ideologies that perpetuate inequality. By amplifying the voices of marginalised women, it calls for a more equitable understanding of identity that transcends political, gender and cultural boundaries, emphasising the necessity of breaking down barriers of exclusion across biblical and contemporary contexts.Contribution: The study contributes significantly to both biblical studies and contemporary social discourse by applying a postcolonial feminist critique to Matthew 15:21–28. The study challenges traditional androcentric and Christ-centric readings of the text that often minimise the Canaanite woman’s voice and agency. By drawing a parallel between the Canaanite woman and North Korean women in South Korea, the study underscores how imperialistic and androcentric systems marginalise women across both biblical and modern contexts.